Transient oxygen uptake response as an indicator of sports specific adaptation - Norris, Stephen R. (My University, 1987)
A cross-sectional design examined aerobic power and transient oxygen uptake responses of four male sports groups (cyclists, runners, swimmers, and cross-country skiers). Data was collected via three modes of ergometry (treadmill running, cycling, and arm cranking), with the transient oxygen uptake responses being described via the 'half-time' (t1/2 VO[subscript 2]on) and 'Mean Response Time' (MRT) values. The transient VO[subscript 2]on responses were quantified via a single exponential process given as [see document for formula] where A reflects the increment above the previous (rest or exercise) steady state level, ss represents the steady State or asymptotic value, TD is the time delay parameter, and T is the time constant...
Keywords: Oxygen Physiological transport